CORRECTION OF KEY ENZYMES BY TIOTSIN IN EXPERIMENTAL MULTIFOCAL ATHEROSCLEROSIS - Akhmatova K.A., Azizova D.M. (Central Asian Journal of Medicine, 2025)
This study investigates the activity of two key enzymes—3-hydroxy-3-methylglutaryl-CoA reductase (HMG-CoA reductase), a major enzyme in cholesterol biosynthesis, and proprotein convertase subtilisin/kexin type 9 (PCSK9), a regulator of lipoprotein metabolism—in an experimental model of multifocal atherosclerosis, and explores the potential for their correction using Tiotsin. The experiment demonstrated a significant increase in HMG-CoA reductase and PCSK9 levels in the context of multifocal atherosclerosis, suggesting disruption of lipid metabolism and acceleration of atherogenesis. Treatment with Tiotsin (a complex of a-lipoic acid and zinc) reduced both expression and activity of these enzymes, leading to a slowdown of the atherosclerotic process. These findings indicate that Tiotsin may be a promising therapeutic agent for correcting atherosclerosis through modulation of HMG-CoA reductase and PCSK9 activity.